Dental care utilization in Massachusetts before and after initiation of medication for opioid use disorder: A cross‐sectional study of a state all‐payer claims database. (23rd November 2021) - Simon, Lisa; Choudhary, Abhishek; Ticku, Shenam; Barrow, Jane; Tobey, Matthew
Abstract: Background: Individuals with opioid use disorder (OUD) are at higher risk of poor oral health. Medication for opioid use disorder (MOUD) has been shown to improve outcomes for patients with OUD, but it is unknown how initiation of MOUD affects access to oral health services. Methods: This was a retrospective analysis of all individuals in the Massachusetts All‐Payer Claims Database prescribed oral buprenorphine‐naloxone or injectable naltrexone from 2013 to 2016. We evaluated dental utilization in the year before and after beginning MOUD. A logistic regression predicting dental utilization was conducted. Results: Among the 54, 791 individuals, rates of dental utilization were low both before and after MOUD (10.5% and 10% with a dental visit, respectively). Of those who did not have a dental visit in the year before starting MOUD, 95.1% did not have a dental visit in the year after. Rates of various procedure types were comparable before and after MOUD. In a logistic regression, a prior dental visit was associated with 9.82 times the odds (95% CI 9.14–10.55) of having a dental visit after starting MOUD; increasing age, being prescribed naltrexone, having a mood disorder or HIV, year of initiation or being on Medicaid were also associated with having a dental visit. Male patients and those with Medicare or private insurance were less likely to have a dental visit. Conclusions: Initiating MOUD did not substantially result in increased dental access or substantial changes in dental procedures received. Patients receiving treatment for OUD may require additional support to access dental care.